Antimicrobial and immunomodulatory activity of natural bioactive compounds – an in vitro investigation with potential applications in managing Hidradenitis Suppurativa - Badaluta, Valentina-Alexandra; Ionascu, Adrian; Ditu, Lia-Mara; Curutiu, Carmen; Holban, Alina-Maria; Oprea, Eliza; Kourkoutas, Yiannis; Mihai, Mara Madalina; Cucu, Corina Ioana; Hudita, Ariana; Marinescu, Florica; Lazar, Veronica (Frontiers in Immunology, 2025)
BackgroundNatural bioactive compounds such as terpenoids and phenolic acids have emerged as promising agents in dermatological research due to their proven antioxidant, antimicrobial and anti-inflammatory properties. Hidradenitis Suppurativa (HS), a chronic inflammatory condition, presents a therapeutic challenge that could benefit from innovative approaches harnessing these natural compounds.ObjectiveThe present study aimed to evaluate the antimicrobial and immunomodulatory effects of phytoconstituent agents (FCs) including Gallic Acid (GA), α–Terpineol (αT) and Nerolidol (N), both individually and in combinations. The potential of these compounds to enhance immune regulation and inhibit biofilm development in HS-related pathogen was explored through in vitro investigations, emphasizing their therapeutic potential in managing HS-related infections and inflammation.MethodsPhytocompounds (FCs) (GA, αT and N) were obtained by solubilization in dimethyl sulfoxide (DMSO) at an initial concentration of 10 mg/mL and tested against standard and clinical strains of HS-associated pathogens. Additionally, Lactic Acid Bacterial (LAB) strains isolated from normal microbiota, dental plaque and lactic fermented foods were assessed for their antimicrobial, anti-biofilm and immunomodulatory effect, using both qualitative and quantitative assays. The immunomodulatory properties were analyzed using macrophages differentiated from THP-1 human monocytic cells. Cytokine modulation was measured via Enzyme-Linked Immunosorbent Assay (ELISA).ResultsThe combination of α-terpineol and nerolidol demonstrated potent antimicrobial activity and markedly inhibiting biofilm development, particularly against Gram-positive bacterial strains. A significant modulation of the inflammatory response, including enhanced IL-10 induction, was observed when Lactobacillus paracasei was combined with either nerolidol or α-terpineol.ConclusionsThese findings underscore the potential of natural bioactive compounds and their combinations as promising candidates for further investigation in managing skin infections and inflammation-related disorders, including HS. Future studies are essential to optimize formulations, evaluate compound stability, cytotoxicity and skin penetration and establish efficacy in vivo, paving the way for the development of well-tolerated and effective topical formulations.